Prognostic impact of clinical factors for immune checkpoint inhibitor with or without chemotherapy in older patients with non-small cell lung cancer and PD-L1 TPS ≥ 50% - Takei, Shota; Kawachi, Hayato; Yamada, Tadaaki; Tamiya, Motohiro; Negi, Yoshiki; Goto, Yasuhiro; Nakao, Akira; Shiotsu, Shinsuke; Tanimura, Keiko; Takeda, Takayuki; Okada, Asuka; Harada, Taishi; et al. (Frontiers in Immunology, 2024)
Introduction The proportion of older patients diagnosed with advanced-stage non-small cell lung cancer (NSCLC) has been increasing. Immune checkpoint inhibitor (ICI) monotherapy (MONO) and combination therapy of ICI and chemotherapy (COMBO) are standard treatments for patients with NSCLC and programmed cell death ligand-1 (PD-L1) tumor proportion scores (TPS) ≥ 50%. However, evidence from the clinical trials specifically for older patients is limited. Thus, it is unclear which older patients benefit more from COMBO than MONO. Methods We retrospectively analyzed 199 older NSCLC patients of Eastern Cooperative Oncology Group performance status (ECOG PS) 0-1 and PD-L1 TPS ≥ 50% who were treated with MONO or COMBO. We analyzed the association between treatment outcomes and baseline patient characteristics in each group, using propensity score matching. Results Of the 199 patients, 131 received MONO, and 68 received COMBO. The median overall survival (OS; MONO: 25.2 vs. COMBO: 42.2 months, P = 0.116) and median progression-free survival (PFS; 10.9 vs. 11.8 months, P = 0.231) did not significantly differ between MONO and COMBO group. In the MONO group, OS was significantly shorter in patients without smoking history compared to those with smoking history [HR for smoking history against non-smoking history: 0.36 (95% CI: 0.16-0.78), P = 0.010]. In the COMBO group, OS was significantly shorter in patients with PS 1 than those with PS 0 [HR for PS 0 against PS 1: 3.84 (95% CI: 1.44-10.20), P = 0.007] and for patients with squamous cell carcinoma (SQ) compared to non-squamous cell carcinoma (non-SQ) [HR for SQ against non-SQ: 0.17 (95% CI: 0.06-0.44), P < 0.001]. For patients with ECOG PS 0 (OS: 26.1 months vs. not reached, P = 0.0031, PFS: 6.5 vs. 21.7 months, P = 0.0436) or non-SQ (OS: 23.8 months vs. not reached, P = 0.0038, PFS: 10.9 vs. 17.3 months, P = 0.0383), PFS and OS were significantly longer in the COMBO group. Conclusions ECOG PS and histological type should be considered when choosing MONO or COMBO treatment in older patients with NSCLC and PD-L1 TPS ≥ 50%.